Antagonistic Endophytic Fungi from Papaya Fruit Against Anthracnose Causing Pathogens (Colletotrichum gloeosporioides) on Papaya Fruit - Nasahi, Ceppy; Amatullah, Hana Lathifah; Kurniadie, Denny (CROPSAVER, 2023)
Anthracnose disease caused by Colletotrichum gloeosporioides considered a major disease on papaya fruit. One way to control plant diseases is to use antagonistic fungi as biocontrol agents. Several antagonistic fungi can be found in plant tissues (endophytic fungi). This study aims to get endophytic fungi from papaya fruit antagonistic to the fungus C. gloeosporioides. The research used a Completely Randomized Design (CRD) consisting of four treatments and five replications on in-vitro and in-vivo tests. The results showed that three isolates of endophytic fungi found from papaya fruit were Fusarium sp., Aureobasidium sp., and Acremonium sp., which had an inhibition of 63.5%, 67.86%, and 7.52%, respectively. Fusarium sp. and Aureobasidium sp. are potentially considered antagonist fungi in controlling the fungus C. gloeosporioides in in-vitro testing based on the inhibition results were more than 60%. Aureobasidium sp. is considered potential antagonist fungi according to the colonization or growth of C. gloeosporioides mycelium inhibition that emerges on papaya up to 97%.